Increasing Language Development Of Children At Kindergaten Age - Maqda Almadina; Lailatul Fadila; Fatima Iriyani Eko (PROCEEDING UMSURABAYA, 2020)
Abstract. Language Development allows children in kindergarten age to learn tounderstand and control themselves. When children learn to talk, they unintentionally develop their knowledge of the primary language for children. Children in their life and environment can develop this knowledge, both at home, in play life, and at school. For kindergarten-age children in school life, the teacher's knowledge of children's language is useful for planning, implementing, and in learning. The development of children's language learning for kindergarten is a teacher who helps in early development. To achieve these goals, then understand the teacher about discussing listening and speaking properly. The teacher's talk in class determines children's oral participation and participation to renew the child's language.Keywords: Language Development, Teachers, Kindergarten Age Children.